2011 Dahlberg Award Winner: Evaluation of the utility of deciduous molar morphological variation in great ape phylogenetic analysis - Anna M. Hardin; Scott S. Legge (Dental Anthropology Association, 2013)
Non-metric dental traits are well-established tools for anthropologists investigating population affiliation and movement in humans. Nonetheless, similar traits in the great apes have received considerably less attention. The present study provides data on non-metric trait variability in the deciduous molars of great apes from museum context. Twenty-eight traits are observed in the upper and lower deciduous molars in specimens of Pan troglodytes, Pan paniscus, Gorilla gorilla, and Gorilla beringei. These groups are compared based on trait frequencies and mean measures of divergence. This study demonstrates the variability of non-metric traits in the deciduous molars of chimpanzees and gorillas. These traits could potentially be used in the same way that non-metric traits are in humans, namely group affiliation and population movements through time. Further, this study establishes scoring guidelines and methodology relevant to deciduous dental morphological characteristics found in the great apes, but not necessarily in humans.